Solution Studies of Some Low-Valent Metal Complexes - Singh, T.K.; Kumar, Ashok (Asian Journal of Chemistry, 2010)
Low-valent metal complexes in solution phase of alkali and alkaline earth metals with unsaturated groups and/or binding site having high electron density formed in non-aqueous solvent have been studied with a view to study the cancerous diseases. The study is based and concluded mainly on pH measurements.